Xenopus tropicalis: Joining the Armada in the Fight Against Blood Cancer - Dimitrakopoulou, Dionysia; Tulkens, Dieter; Van Vlierberghe, Pieter; Vleminckx, Kris (Frontiers in Physiology, 2019)
Aquatic vertebrate organisms such as zebrafish have been used for over a decade to model different types of human cancer, including hematologic malignancies. However, the introduction of gene editing techniques such as CRISPR/Cas9 and TALEN, have now opened the road for other organisms featuring large externally developing embryos that are easily accessible. Thanks to its unique diploid genome that shows a high degree of synteny to the human, combined with its relatively short live cycle, Xenopus tropicalis has now emerged as an additional powerful aquatic model for studying human disease genes. Genome editing techniques are very simple and extremely efficient, permitting the fast and cheap generation of genetic models for human disease. Mosaic disruption of tumor suppressor genes allows the generation of highly penetrant and low latency cancer models. While models for solid human tumors have been recently generated, genetic models for hematologic malignancies are currently lacking for Xenopus. Here we describe our experimental pipeline, based on mosaic genome editing by CRISPR/Cas9, to generate innovative and high-performing leukemia models in Xenopus tropicalis. These add to the existing models in zebrafish and will extend the experimental platform available in aquatic vertebrate organisms to contribute to the field of hematologic malignancies. This will extend our knowledge in the etiology of this cancer and assist the identification of molecular targets for therapeutic intervention.